Cấu trúc và hoạt tính quang xúc tác của bột nano W-TiO2 được điều chế bằng phương pháp ướt - Hưng, Nguyễn Văn; Thanh Lê, Đặng Thị (Vietnam Journal of Chemistry, 2014)
Tungsten-doped nanosized TiO2 powders were synthesized by a simple wet method, and characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) and UV-Vis diffuse reflectance spectra (UV-Vis DRS). The photocatalytic activity of undoped TiO2 and W-doped TiO2 photocatalysts was evaluated by the photocatalytic oxidation of methylene blue in aqueous solution under visible light irradiation to study the influence of the tungsten doping degree on the photocatalytic degradation performance of TiO2. The results showed that the photocatalytic activity of the W-doped TiO2 photocatalyst is much higher than that of undoped TiO2, and the optimum W/Ti molar ratio is 0.5%. Moreover, the study also showed that, the doping W atoms suppress the growth of the TiO2 crystal and phase transformation. Keywords: Titanium dioxide, Tungsten, photocatalyst, W-doped TiO2, methylene blue, wet method.